The Influence of Online Transaction Security and Live Streaming on Online Purchasing Decisions (A Study of MSME Consumers in Palangkaraya City) - Sucidha, Irma; Yuliani, Yuliani (The Es Economics and Entrepreneurship, 2025)
The phenomenon of online shopping seems to be increasingly prevalent among buyers. Besides the convenience of transactions, buyers are also faced with various questions regarding product clarity, sellers, security, and other aspects not found in conventional sales. This study aims to determine the influence of online transactions on online purchasing decisions, as well as the influence of live streaming on online purchasing decisions. From 128 samples taken from Palangkaraya City residents who have made online purchases, it was found that both online transactions and live streaming variables were able to influence consumers' online purchasing decisions.